Evaluation of retinal structural and microvascular changes in patients with acute pancreatitis - Büşra Dilara Yıldırım Erdal; Harun Erdal (Photodiagnosis and Photodynamic Therapy)
Background: This study aimed to show the changes in retinal vascular densities and thicknesses in the peripapillary and macular regions in the acute period in patients with acute pancreatitis (AP). Methods: This prospective cross-sectional study included 57 eyes of 30 patients with AP and 58 eyes of 30 healthy people. Optical coherence tomography angiography (OCTA) was taken within 24–72 h of AP patients’ hospitalization. OCTA was used to evaluate the retinal microvascular structure and retinal thickness. Results: Peripapillary retinal nerve fiber layer (pp-RNFL) and perifoveolar ganglion cell complex (pef-GCC) thickness in patients with AP were significantly higher than in the healthy control group (p = 0.020 and p = 0.039, respectively). While whole image vessel density (wiVD) and perifoveal vessel density (pefVD) were significantly lower in the deep capillary plexus (DCP), choriocapillaris flow area (CCFA) in the macula were significantly lower in each of the 1 mm and 3 mm radius areas in patients with AP (p = 0.014, p = 0.011; p = 0.011, and p = 0.035 respectively). In the univariable and multivariable linear regression analysis, it was observed that serum lipase and procalcitonin levels affected the thickness of pp-RNFL and pef-GCC (for pp-RNFL, β= 0.001, p = 0.002, β=24.992, p < 0.001, and for pef-GCC, β= 0.001 p = 0.014, β=17.107 p < 0.001 respectively). Conclusions: There are significant microvascular and structural changes in the optic nerve and macula in patients with AP. The relationship between these changes and serum lipase and procalcitonin levels was shown. Clinicians should consider ocular involvement in AP patients with high serum lipase and procalcitonin levels.